2023
DOI: 10.2147/jir.s400115
|View full text |Cite
|
Sign up to set email alerts
|

Common Variables That Influence Sepsis Mortality in Mice

Abstract: Sepsis is characterized by a dysregulated host immune response to infection, leading to organ dysfunction and a high risk of death. The cecal ligation and puncture (CLP) mouse model is commonly used to study sepsis, but animal mortality rates vary between different studies. Technical factors and animal characteristics may affect this model in unanticipated ways, and if unaccounted for, may lead to serious biases in study findings. We sought to evaluate whether mouse sex, age, weight, surgeon, season of experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
(64 reference statements)
1
7
0
Order By: Relevance
“…Although we agree that the CLP model may yield variable results according to these factors, the same can be said for many animal models, as well as clinical conditions among different study populations. Our study 1 essentially highlights biological and technical variables that influence sepsis mortality and does not construe a criticism of the CLP model, and this was not implied in our manuscript. Instead, our report 1 was intended to reveal some essential characteristics of animals and the laboratory environment that should be considered in the experimental design for sepsis studies.…”
Section: Dear Editormentioning
confidence: 95%
See 2 more Smart Citations
“…Although we agree that the CLP model may yield variable results according to these factors, the same can be said for many animal models, as well as clinical conditions among different study populations. Our study 1 essentially highlights biological and technical variables that influence sepsis mortality and does not construe a criticism of the CLP model, and this was not implied in our manuscript. Instead, our report 1 was intended to reveal some essential characteristics of animals and the laboratory environment that should be considered in the experimental design for sepsis studies.…”
Section: Dear Editormentioning
confidence: 95%
“…Our study 1 essentially highlights biological and technical variables that influence sepsis mortality and does not construe a criticism of the CLP model, and this was not implied in our manuscript. Instead, our report 1 was intended to reveal some essential characteristics of animals and the laboratory environment that should be considered in the experimental design for sepsis studies. Our report 1 found that sepsis mortality rates were influenced by the timing of antibiotic administration, animal weight and the season (summer vs non-summer seasons), and this occurred differently in males vs females.…”
Section: Dear Editormentioning
confidence: 95%
See 1 more Smart Citation
“…We read with interest the study by Garcia et al, “Common Variables That Influence Sepsis Mortality in Mice”. 1 Based on their own experience, authors identified some factors specific to sex and season that significantly influence sepsis mortality in the CLP model, therefore questioning the status of this model as the gold standard in preclinical research on sepsis.…”
Section: Dear Editormentioning
confidence: 99%
“…The sham-operated group received only 50-ml/kg saline immediately, and 12 h after surgery, and the volume of saline corresponded to antibiotic administration (Hubbard et al, 2005). The mortality rate of CLPinduced rats was around 30%, according to the literature (Garcia et al, 2023).…”
Section: Clp Modelmentioning
confidence: 99%